Prospects and Constraints of Crab Culture in Wetlands of Bihar, India - Tiwary, N.P.; Kumar, P.; Prasad, R.R.; Kumari, M.; Kumar, R. (Our Nature, 2010)
This paper deals with the prospects and constraints of crab culture in wetlands of Bihar, India. Key words: Wetland, Crab culture, Paratelphusa spinigera, Pens, Cages, Juveniles, Water crabs DOI: 10.3126/on.v7i1.2578 Our Nature (2009) 7:230-232